RESENHA: MACDOUGALL,D. The looking machine: Essays on cinema, anthropology and documentary filmmaking (Anthropology, Creative Practice and Ethnography). Manchester University Press. 2019 - Camillo, Camille Sant’Anna (Revista Avesso: Pensamento, Memória e Sociedade, 2020)
Resenha do livro: MACDOUGALL,D. The looking machine: Essays on cinema, anthropology and documentary filmmaking (Anthropology, Creative Practice and Ethnography). Manchester University Press. 2019